Preanesthetic assessment data do not influence the time for tracheal intubation with Airtraq(tm) video laryngoscope in obese patients - Ranieri Jr.,Dante (2014)
Purpose: this study investigated the influence of anatomical predictors on difficult laryngoscopy and orotracheal intubation in obese patients by comparing Macintosh and Airtraq(tm) laryngoscopes. Methods: from 132 bariatric surgery patients (body mass index = 35 kg m-1), cervical perimeter, sternomental distance, interincisor distance, and Mallampati score were recorded. The patients were randomized into two groups according to whether a Macintosh (n = 64) or an Airtraq(tm) (n = 68) laryngoscope was used for tracheal intubation. Time required for intubation was the first outcome. Cormack-Lehane score, number of intubation attempts, the Macintosh blade used, any need for external tracheal compression or the use of gum elastic bougie were recorded. Intubation failure and strategies adopted were also registered. Results: intubation failed in two patients in the Macintosh laryngoscope group, and these patients were included as worst cases scenario. The intubation times were 36.9 + 22.8 s and 13.7 + 3.1 s for the Macintosh and Airtraq(tm) laryngoscope groups (p < 0.01), respectively. Cormack-Lehane scores were also lower for the Airtraq(tm) group. One patient in the Macintosh group with intubation failure was quickly intubated with the Airtraq(tm). Cervical circumference (p < 0.01) and interincisor distance (p < 0.05) influenced the time required for intubation in the Macintosh group but not in the Airtraq(tm) group. Conclusion: in obese patients despite increased neck circumference and limited mouth opening, the Airtraq(tm) laryngoscope affords faster tracheal intubation than the Macintosh laryngoscope, and it may serve as an alternative when conventional laryngoscopy fails.